Associations of number of victimizations with mental health indicators and health-risk behaviours among a nationally representative sample of in-school adolescents in Curaçao. (January 2021) - Pengpid, Supa; Peltzer, Karl
Abstract: Purpose: The study aimed to estimate the association of experiencing a higher number of victimizations with mental health and health-risk behaviours among adolescents in the 2015 Curaçao Global School-Based Student Health Survey (GSHS). Methods: In all, 2, 765 in-school adolescents with a median age of 15 years from Curaçao responded to the cross-sectional GSHS. Results: Results indicate that from six forms of victimization (bullied, parental physical victimization, physically attacked, physical intimate partner violence victimization, forced sex and violent injury) assessed, 29.6 % reported one type of victimization, 11.3 % two types and 4.9 % three or more types of victimization. In adjusted logistic regression analyses, PV was associated with four poor mental health indicators (worry-induced sleep disturbance, suicidal ideation, loneliness, and suicide attempt) and eleven health-risk behaviours (current tobacco use, current alcohol use, current cannabis use, early sexual debut, sex among students who were drunk, multiple sexual partners, non-condom use at last sex, school truancy, carrying a weapon, short sleep and skipping breakfast). Conclusion: Almost one in six students reported poly-victimization (≥2 types). Higher frequency of victimization was positively associated with four poor mental health indicators and eleven health-risk behaviours.